Lithium ion battery electrolyte and preparation method thereof
By adding a specific proportion of organic solvents, lithium salts and film-forming additives to the lithium-ion battery electrolyte, the problems of flammability, unstable low-temperature performance and low charging efficiency of the electrolyte are solved, and the low-temperature fast charging performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411033842.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery electrolytes have problems such as flammability, unstable low-temperature performance and low charging efficiency.
The electrolyte including organic solvents, lithium salts and film-forming additives is used to improve the low-temperature performance and flame retardant properties of the electrolyte by adjusting the mass ratio of the organic solvents to the film-forming additives and the molar concentration of the lithium salt.
It significantly improves the battery's low-temperature fast charging capability, broadens application scenarios, improves the overall performance stability and safety of the battery, and extends the battery's service life.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery electrolyte and a preparation method thereof. Background Art
[0002] With the continuous growth of the global economy and the continuous expansion of the population, the demand for energy has increased dramatically. At the same time, environmental problems have become increasingly severe, forcing the global society to transform to a green, low-carbon, and sustainable energy system. As an efficient and environmentally friendly energy storage method, lithium-ion batteries stand out from many energy storage technologies and are gradually becoming an important support in the field of new energy. They have become a key force in promoting the development of new energy vehicles, smart grids, portable electronic devices and other fields. However, lithium-ion batteries currently still have bottlenecks in three aspects: low temperature, fast charging and flame retardancy.
[0003] First of all, traditional lithium-ion batteries have significant limitations in the working environment temperature, and their normal operating temperature range is usually limited to a relatively narrow range, generally -20 to 55°C. Under extreme climatic conditions, such as cold winters or low-temperature environments such as high altitudes and polar regions, the internal chemical reaction rate slows down and the fluidity of the electrolyte decreases, resulting in the obstruction of the migration of lithium ions between electrode materials, which in turn significantly reduces the discharge capacity of the battery. Data show that when working at -20°C, the discharge capacity of lithium-ion batteries is only about 70% of that at room temperature. In addition, since the electrolyte usually contains flammable organic solvents and thermally unstable lithium salts, thermal runaway is very likely to occur, and even fire or explosion, posing a huge threat to personal safety and the environment. Therefore, the development of a lithium-ion battery electrolyte with flame retardancy, fast charging and stable low-temperature performance is of great significance to promoting the development of green energy. Summary of the invention
[0004] The object of the present invention is to provide a lithium ion battery electrolyte and a preparation method thereof, so as to solve the problems of flammability, unstable low temperature performance and low charging efficiency existing in the existing lithium ion battery electrolyte.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A lithium ion battery electrolyte comprising an organic solvent, a lithium salt and a film-forming additive;
[0007] The mass ratio of the organic solvent to the film-forming additive is 10 to 20:1;
[0008] The molar concentration of the lithium salt is 0.5 to 1.5 mol / L.
[0009] Furthermore, the mass ratio of the organic solvent to the film-forming additive is 10 to 10.5:1.
[0010] Furthermore, the organic solvent is a linear carboxylate or linear carbonate compound.
[0011] Furthermore, the organic solvent is one or a combination of methyl propionate, vinylene carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl acetate and methyl trifluoroethyl carbonate.
[0012] Furthermore, the film-forming additive is one or a combination of vinylene carbonate, fluoroethylene carbonate, lithium difluorooxalatoborate and propylene sulfite.
[0013] Furthermore, the lithium salt is one or a combination of lithium hexafluorophosphate, lithium dioxalatoborate, lithium tetrafluoroborate and lithium difluorooxalatoborate.
[0014] A method for preparing the lithium ion battery electrolyte comprises:
[0015] The organic solvent, the film-forming additive and the lithium salt are mixed, stirred evenly and allowed to stand to obtain a lithium-ion battery electrolyte.
[0016] Furthermore, the stirring speed is 100 r / min, the stirring time is 8 h, and the reaction temperature is room temperature.
[0017] Furthermore, the standing time is 5 hours.
[0018] A button-type lithium metal battery is made from the lithium-ion battery electrolyte.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention provides a lithium ion battery electrolyte, comprising a lithium salt with a molar concentration of 0.5 to 1.5 mol / L, and an organic solvent and a film-forming additive in a mass ratio of 10 to 20:1. The present invention introduces a film-forming additive with good compatibility with the organic solvent, which not only improves the low-temperature performance of the electrolyte, helps the electrolyte to maintain fluidity at a relatively low temperature, but also promotes the rapid transmission of lithium ions under low temperature conditions, thereby significantly improving the low-temperature fast charging capability of the battery and broadening the application scenarios of the battery, especially the performance in cold environments. It also improves the compatibility of the electrode and successfully breaks through the limitation that the organic solvent cannot be used as the main solvent of the electrolyte, which helps to reduce the side reactions between the electrode and the electrolyte, prolong the service life of the battery, and improve the overall performance stability of the battery. At the same time, the use of a low melting point and Li +The use of an organic solvent with low desolvation energy as the main solvent and a film-forming additive promotes the formation of a high-performance solid electrolyte interface film (SEI film) and a stable cathode electrolyte interface film (CEI film). These interface films can protect the electrode from the erosion of the electrolyte, while providing a fast lithium ion transmission channel, accelerating the lithium ion transmission rate, thereby significantly improving the low-temperature fast charging performance and cycle stability of the battery. The present invention solves the problems of flammability, unstable low-temperature performance and low charging efficiency of existing lithium-ion battery electrolytes, and can form a solid, uniform and relatively thin solid electrolyte interface film on the surface of the electrode material, thereby improving the cycle life and capacity of the lithium-ion battery.
[0021] The present invention selects highly compatible flame retardant components to make them compatible in the electrolyte and have a significantly higher ignition point than commercial electrolytes. By introducing fluorine- and boron-containing additives, the chain reaction of the flame is destroyed, thereby greatly improving the flame retardant properties of the electrolyte and ensuring the safety and stability of the battery under high temperature conditions. This is of great significance for improving the safety of batteries in applications such as electric vehicles and energy storage systems, and provides strong support for the advancement of lithium-ion battery technology and the expansion of its applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] FIG1 is a full-battery room-temperature cycle charge-discharge test curve of a button-type lithium metal battery prepared in Example 7 of the present invention.
[0024] Figure 2 This is a 30-cycle charge-discharge specific capacity diagram of Example 7 of the present invention.
[0025] Figure 3 This is a graph showing the relationship between full battery efficiency and cycle number at room temperature for Example 7 of the present invention and a control group.
[0026] FIG. 4 is a scanning electron microscope image of the positive electrode film of Example 7 of the present invention.
[0027] FIG5 is a scanning electron microscope image of the positive electrode film of the control group of the present invention.
[0028] Figure 6 This is a characterization diagram of the negative electrode of Example 7 of the present invention.
[0029] Figure 7 It is a negative electrode characterization diagram of the control group of the present invention.
[0030] FIG8 is a graph showing the battery efficiency and cycle number of the full battery and normal battery prepared in Example 7 of the present invention and the control group battery at low temperature.
[0031] Fig. 9 Graph showing the charge and discharge efficiency and cycle number of Example 7 and the control group under extreme conditions of the present invention.
[0032] Fig.10 Graph showing the initial charge-discharge capacity of Example 7 of the present invention and the control group. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0041] The invention provides a lithium ion battery electrolyte, comprising the following components: an organic solvent, an additive and a lithium salt.
[0042] The mass ratio of the organic solvent to the additive is 10 to 20:1, preferably 10 to 15:1, more preferably 10 to 12.5:1, and even more preferably 10 to 10.5:1;
[0043] The molar concentration of the lithium salt is 0.5 to 1.5 mol / L, preferably 0.5 mol / L, 0.7 mol / L, 0.8 mol / L, 1.0 mol / L or 1.2 mol / L.
[0044] The organic solvent is a linear carboxylic acid ester or a linear carbonate compound, specifically one or a combination of methyl propionate, vinylene carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl acetate and methyl trifluoroethyl carbonate.
[0045] The additive is one or a combination of vinylene carbonate, fluoroethylene carbonate, lithium difluorooxalatoborate and propylene sulfite.
[0046] The lithium salt is one or a combination of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium difluorooxalatoborate.
[0047] The present invention also provides a method for preparing a lithium ion battery electrolyte, comprising the following steps:
[0048] The organic solvent, additive and lithium salt are mixed according to a proportion, stirred continuously at 100 r / min for 8 hours at room temperature, and allowed to stand for 5 hours before being mixed evenly to obtain a lithium-ion battery electrolyte.
[0049] The technical solution of the present invention is further described below through specific embodiments:
[0050] Embodiment 1:
[0051] In a glove box filled with argon gas and with water and oxygen content less than 1 ppm, a solution with a mass ratio of organic solvent to film-forming additive of 100:9 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 95:5, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0052] Embodiment 2:
[0053] In a glove box filled with argon gas and with water and oxygen content less than 1 ppm, a solution with a mass ratio of organic solvent to film-forming additive of 100:8.1 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 95:5, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0054] Embodiment 3:
[0055] In a glove box filled with argon gas and with water and oxygen content less than 1 ppm, a solution with a mass ratio of organic solvent to film-forming additive of 100:9.9 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 95:5, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0056] Embodiment 4:
[0057] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solution with a mass ratio of 100:9 of organic solvent to film-forming additive was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 90:10, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0058] Embodiment 5:
[0059] In a glove box filled with argon gas and with water and oxygen content less than 1 ppm, a solution with a mass ratio of organic solvent to film-forming additive of 100:9 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 97:3, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0060] Embodiment 6:
[0061] In a glove box filled with argon gas and with water and oxygen content less than 1 ppm, a solution with a mass ratio of organic solvent to film-forming additive of 100:9 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 95:5, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 0.8 mol·L -1After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0062] Embodiment 7:
[0063] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solution with a mass ratio of organic solvent to film-forming additive of 100:9 was prepared, wherein the mass ratio of methyl propionate to vinylene carbonate in the organic solvent was 95:5, and the mass ratio of fluoroethylene carbonate to propylene sulfite to lithium difluorooxalate borate in the film-forming additive was 1:1:1. Lithium hexafluorophosphate was added to the electrolyte solvent to a concentration of 1.2 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, and placed in a heat-collecting constant temperature heating magnetic stirrer. Stir continuously at 100r / min for 8 hours at room temperature, and after standing for 5 hours, mix evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium metal battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0064] Embodiment 8:
[0065] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of 100:8 of organic solvent:film-forming additive was taken, wherein the mass ratio of propylene carbonate:ethylene carbonate:diethyl carbonate:ethyl acetate:methyl propionate in the organic solvent was 1:1:1:2:1, and the mass ratio of fluoroethylene carbonate:propylene sulfite:vinyl carbonate in the film-forming additive was 3:3:2. Lithium salts: lithium tetrafluoroborate and lithium difluorooxalatoborate were added to the electrolyte solvent, so that their concentrations in the electrolyte were 0.5 mol·L -1 and 0.5 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0066] Embodiment 9:
[0067] In a glove box filled with argon gas and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of 100:8 of organic solvent:film-forming additive was taken, wherein the mass ratio of propylene carbonate:ethylene carbonate:diethyl carbonate:ethyl acetate:methyl propionate in the organic solvent was 20.6:12.6:16.6:33.3:16.6, and the mass ratio of fluoroethylene carbonate:propylene sulfite:vinyl carbonate in the film-forming additive was 3:3:2. Lithium salts: lithium tetrafluoroborate and lithium difluorooxalatoborate were added to the electrolyte solvent, so that their concentrations in the electrolyte were 0.5 mol·L -1 and 0.5 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0068] Embodiment 10:
[0069] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of 100:8 of organic solvent:film-forming additive was taken, wherein the mass ratio of propylene carbonate:ethylene carbonate:diethyl carbonate:ethyl acetate:methyl propionate in the organic solvent was 20.6:16.6:16.6:29.3:16.6, and the mass ratio of fluoroethylene carbonate:propylene sulfite:vinyl carbonate in the film-forming additive was 3:3:2. A certain mass of lithium salts: lithium tetrafluoroborate and lithium difluorooxalate borate were added to the electrolyte solvent, so that their concentrations in the electrolyte were 0.5 mol·L -1 and 0.5 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0070] Embodiment 11:
[0071] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of 100:8 of organic solvent:film-forming additive was taken, wherein the mass ratio of propylene carbonate:ethylene carbonate:diethyl carbonate:ethyl acetate:methyl propionate in the organic solvent was 1:1:1:2:1, and the mass ratio of fluoroethylene carbonate:propylene sulfite:vinyl carbonate in the film-forming additive was 3:3:2. Lithium dioxalatoborate was added to the electrolyte solvent to a concentration of 0.7 mol·L-1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0072] Embodiment 12:
[0073] In a glove box filled with argon and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of 100:8 of organic solvent:film-forming additive was taken, wherein the mass ratio of propylene carbonate:ethylene carbonate:diethyl carbonate:ethyl acetate:methyl propionate in the organic solvent was 1:1:1:2:1, and the mass ratio of fluoroethylene carbonate:propylene sulfite:vinyl carbonate in the film-forming additive was 3:3:2. Lithium dioxalatoborate was added to the electrolyte solvent to a concentration of 1.0 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this example is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0074] Embodiment 13:
[0075] In a glove box filled with argon gas and containing less than 1 ppm of water and oxygen, a solid having a mass ratio of organic solvent to film-forming additive of 20:1 was taken, wherein the mass ratio of fluoroethylene carbonate to methyl trifluoroethyl carbonate in the organic solvent was 1:1, and the mass ratio of propylene sulfite to vinylene carbonate in the film-forming additive was 3:2. Lithium salts: lithium tetrafluoroborate and lithium difluorooxalatoborate were added to the electrolyte solvent, so that their concentrations in the electrolyte were 0.5 mol·L -1 and 0.5 mol·L -1 After the configuration is completed, the bottle mouth is sealed with insulating tape, taken out from the glove box, placed in a heat-collecting constant temperature heating magnetic stirrer, stirred continuously at 100r / min for 8h at room temperature, and after standing for 5h, mixed evenly to obtain a lithium-ion battery electrolyte. The lithium-ion battery electrolyte prepared in this embodiment is assembled into a button-type lithium-ion battery with the positive electrode CLUDE NCM811 and the lithium metal negative electrode.
[0076] The present invention sets a control group, which is a commercial electrolyte formula. At room temperature, the button-type lithium metal battery obtained in Example 7 is subjected to a battery performance test and compared with the control group. The battery performance test includes a conductivity test, a room temperature cycle charge and discharge performance test, a room temperature negative electrode compatibility test, a room temperature full battery compatibility test, a positive electrode morphology analysis, and a negative electrode characterization test.
[0077] (1) Conductivity test: Take 3 ml of the prepared electrolyte in a plastic test tube and place it in a heat-collecting constant temperature heating magnetic stirrer to maintain a constant temperature of 25°C. Insert the measuring head of the conductivity meter into the electrolyte to measure the conductivity. Wait for about 30 minutes and read the value when it stabilizes.
[0078] (2) Normal temperature cyclic charge and discharge performance test: The battery was placed in a battery temperature cycle tester and the temperature of the tester was adjusted to 25°C. After standing for 8 hours, the battery charge and discharge voltage range was set to 3.0-4.3V. The current density was first set to 0.01C. Two cycles were performed to activate the battery. Then, a large current was used to perform multiple charge and discharge cycles to complete the constant temperature and constant voltage charge and discharge performance test. The test voltage was 3.0-4.3V and the test current was 2.156mA (2C).
[0079] (3) Room temperature negative electrode compatibility test: The positive electrode is copper foil, the negative electrode is lithium metal, and the test current is 2mA / cm 2 The negative electrode compatibility test was carried out under room temperature conditions.
[0080] (4) Normal temperature full battery compatibility test: The thick lithium sheet with a negative electrode thickness of 450 μm in the lithium ion battery was replaced with a thin lithium sheet of 50 μm, and the lithium ion battery assembly process in Examples 1 to 13 was followed to perform a constant temperature and constant voltage charge and discharge compatibility test, wherein the test voltage was 3.0 to 4.3 V and the test current was 2.156 mA / cm 2 , the conditions are normal temperature and pressure.
[0081] (5) Analysis of positive electrode morphology: Pry open the battery shell, take out the positive electrode, and rinse the residual electrolyte on the surface of the positive electrode with dimethyl carbonate reagent. Put the positive electrode into the glove box, and after the surface of the positive electrode is dried, use scissors to cut off the peripheral area of the positive electrode film, leaving the most central rectangular area. Paste conductive glue on the sample table, and paste the cut samples on the conductive glue in sequence. Use a gold sprayer to spray gold on the surface of the treated positive electrode, and then use an electron microscope to observe the morphology of CEI on the surface of the positive electrode.
[0082] (6) Negative electrode characterization test: Pry open the battery shell, quickly put the pried open battery shell into the glove box, take out the negative electrode lithium metal, and rinse the residual electrolyte on the surface of the lithium metal with dimethyl carbonate reagent. After the lithium metal surface is dried, use scissors to cut off the surrounding area of the lithium metal, leaving the most central rectangular area. Paste conductive glue on the sample table, and paste the cut samples on the conductive glue in sequence. Use a gold sprayer to spray gold on the surface of the treated lithium metal, and then use an electron microscope to observe the morphology of SEI on the lithium metal surface.
[0083] The room temperature cyclic charge and discharge test curve of the button-type lithium metal battery prepared in Example 7 is shown in Figure 1. It can be seen from Figure 1 that the charging and discharging states in the room temperature cyclic charge and discharge test curve of Example 7 are symmetrical and uniform and remain stable, indicating that the cycle performance of Example 7 is stable and good. In practical applications, the battery has a longer service life.
[0084] The average discharge capacity of the whole battery is Figure 2 As shown, through Figure 2 It can be seen that the charge-discharge specific capacity of Example 7 is above 260 mAh / g, and the efficiency is maintained at about 99.8%. The relationship between the full battery efficiency and the number of cycles is shown in the figure below: Figure 3 As shown, through Figure 3 In the case of insufficient lithium ion content, it can be seen that the initial efficiency of the control group battery is only about 90%, and the efficiency drops sharply at the 75th cycle, showing an overall downward trend; while the battery efficiency of Example 7 is stable at close to 100%, it can be seen that the SEI film is stable, lithium ion consumption is small, and long-cycle efficiency is well maintained. In practical applications, the cost of lithium metal can be saved and the battery can be used for a longer time. The scanning electron microscopy results of the positive electrode membrane of Example 7 and the control group are shown in Figures 4 and 5. By comparing Figures 4 and 5, it can be seen that the surface impurities of the positive electrode electrolyte interface membrane (CEI) of the control group are seriously deposited, and there are a large number of cracks, while the surface of the CEI membrane of Example 7 is uniform and crack-free, and the particles are dense and compact. It can be obtained that the CEI membrane of Example 7 is excellent in characterization. The characterization results of the negative electrode of Example 7 and the control group are shown in Figures 4 and 5. Figure 6 and Figure 7 As shown, through Figure 6 and Figure 7 In contrast, it was observed that the control group had a lot of lithium dendrites and "dead lithium", which were the products of the reaction between the electrolyte and the lithium metal negative electrode. The continuous occurrence of side reactions would continuously consume lithium metal and electrolyte, resulting in a decrease in CE. At the same time, the growth of lithium dendrites may pierce the diaphragm, resulting in a short circuit, and the thickness of the reactant was 86.2μm. In contrast, Example 7 formed a dense and uniform negative electrode solid electrolyte interface film (SEI), and the lithium deposition morphology was flat, which reduced the side reactions between the electrolyte and the lithium metal negative electrode, indicating that the negative electrode performance of Example 7 was good.
[0085] The fast charging performance test was carried out on Example 7 and the control group, and the tests mainly included low-temperature cycle charge and discharge performance test and extreme low-temperature environment test.
[0086] (1) Low temperature cycle charge and discharge performance test: The cycle charge and discharge performance test of ordinary batteries and full batteries is carried out in a low temperature environment of -20℃.
[0087] (2) Extreme low temperature environment test: The batteries of Example 7 and the control group were placed in a liquid nitrogen tank at -120°C for 1 minute, and then subjected to a charge and discharge cycle test.
[0088] The battery efficiency and cycle number of the full battery prepared in Example 7, the normal battery and the control group battery are shown in Figure 8. It can be observed from Figure 8 that the low-temperature battery performance of Example 7 is stable and relatively superior, with no significant difference from that at room temperature; although the efficiency of the full battery fluctuates greatly, the overall performance is good, and the average efficiency is close to 100%; the low-temperature battery performance of the control group is poor, and there are abnormalities in charging and discharging. The charge and discharge efficiency and cycle number of Example 7 and the control group under extreme conditions are shown in Figure 8. Fig. 9 As shown, the average charge and discharge specific capacity is Fig.10 As shown, through Fig. 9 and Fig.10 It can be observed that the voltage of most of the control group batteries continued to drop and could not be charged; the charge and discharge capacity of a small number of batteries was around 0.002 mAh, approaching 0; while the charge and discharge curve of Example 7 was stable, although the overall charge and discharge capacity decreased slightly, the overall performance was good. It can be concluded that in an extreme low temperature environment (-120°C), the commercial control group batteries were completely inactivated, while the batteries of Example 7 performed well.
[0089] The flame retardant test was performed on Example 7 and the control group. The specific operation steps are as follows: 300 μL of electrolyte was taken into the positive electrode shell with a pipette and placed on the asbestos net of the tripod. The electrolyte in the positive electrode shell was ignited with a high-temperature flamethrower, and the stopwatch was pressed at the same time to measure the burning time of the electrolyte. The flame of the electrolyte in the control group was extinguished after 55 seconds, while it only took 32 seconds for Example 7, the flame extinguishing time was shortened by 23 seconds, and the flame retardant effect was improved by 41.8%.
[0090] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium ion battery electrolyte, characterized in that: including organic solvents, lithium salts and film-forming additives; The mass ratio of the organic solvent to the film-forming additive is (10-20):1; The molar concentration of the lithium salt is 0.5 to 1.5 mol / L.
2. A lithium ion battery electrolyte according to claim 1, characterized in that: The mass ratio of the organic solvent to the film-forming additive is (10-10.5):
1.
3. A lithium ion battery electrolyte according to claim 1, characterized in that: The organic solvent is a linear carboxylic acid ester or a linear carbonate compound.
4. A lithium ion battery electrolyte according to claim 3, characterized in that: The organic solvent is one or a combination of methyl propionate, vinylene carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl acetate and methyl trifluoroethyl carbonate.
5. A lithium ion battery electrolyte according to claim 1, characterized in that: The film-forming additive is one or a combination of vinylene carbonate, fluoroethylene carbonate, lithium difluorooxalatoborate and propylene sulfite.
6. A lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is one or a combination of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium difluorooxalatoborate.
7. A method for preparing a lithium ion battery electrolyte according to any one of claims 1 to 6, characterized in that: include: The organic solvent, the film-forming additive and the lithium salt are mixed, stirred evenly and allowed to stand to obtain a lithium-ion battery electrolyte.
8. The method for preparing a lithium ion battery electrolyte according to claim 7, characterized in that: The stirring speed is 100 r / min, the stirring time is 8 h, and the reaction temperature is room temperature.
9. The method for preparing a lithium ion battery electrolyte according to claim 7, characterized in that: The standing time is 5h.
10. A button-type lithium metal battery, characterized in that: Made from the lithium ion battery electrolyte according to any one of claims 1 to 6.
Citation Information
Patent Citations
Electrolyte and lithium ion battery using electrolyte
CN106450454A
Ternary positive-electrode material based lithium ion battery electrolyte and lithium ion battery with same
CN107293791A